Multifid Iliopsoas Tendons Are More Common in Patients With Painful Snapping Iliopsoas Tendons - Alan Hwang, M.D.; Maximilian Martinez, M.D.; Courtney Marie Cora Jones, Ph.D., M.P.H.; Brian Giordano, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2023)
Purpose: To retrospectively determine the prevalence of multifid tendons in a population of patients who underwent iliopsoas release for painful snapping iliopsoas tendons. Methods: Patients who underwent iliopsoas release for painful snapping iliopsoas tendons were retrospectively identified from a database of patients who had undergone arthroscopic hip surgery performed by a single surgeon between 2011 and 2020. Patients who had incomplete data or who underwent prior fracture fixation, joint arthroplasty, pelvic surgery, or other interventions for snapping hip were excluded. Magnetic resonance imaging (MRI) and operative reports were reviewed and compared with those of an age-matched control group of patients who had undergone hip or pelvic MRI examinations in the past year for different indications. Results: This study included 91 patients (78 female and 13 male patients; mean age, 23.3 years) who were treated operatively for painful snapping hip and 78 controls (54 female and 24 male patients; mean age, 28.4 years) who received hip or pelvic MRI for other indications. Among the patients who underwent iliopsoas release, there were 5 unifid iliopsoas tendons (5.5%) compared with 86 multifid iliopsoas tendons (94.5%) when classified with MRI whereas operative examination showed 19 unifid tendons (20.9%) compared with 72 multifid tendons (79.1%, P < .001). When the MRI scans of the operative group were compared with the MRI scans of the control group, the patients who underwent surgery for painful snapping hip had a higher rate of multifid tendons (94.5% of operative hips compared with 69.2% of control right hips [P < .001] and 74.4% of control left hips [P < .001]). However, when the operative reports were used to classify the iliopsoas tendon, there was no significance between the operative and control groups (79.1% of operative hips had multifid tendons compared with 69.2% of control right hips [P = .141] and 74.4% of control left hips [P = .464]). Conclusions: For patients with symptomatic snapping hip undergoing iliopsoas lengthening, multifid iliopsoas tendons are more prevalent than in a control population. Level of Evidence: Level IV, prognostic case series.